Community Assistance in Preparing Local Resources-Based Organic Agricultural Production Facilities - Dance Tangkesalu; Moh. Hibban Toana; Flora Pasaru; Burhanuddin Haji Nasir; Mohammad Yunus (LPPM Universitas Ma Chung, 2022)
The decreased soil carrying capacity is due to reduced soil organic matter content, caused by disproportionally larger use of inorganic fertilizers and synthetic chemical pesticides in farming activities than organic fertilizers and environmentally friendly weeds, disease, and insect pests control materials. Reducing the use of inorganic fertilizers and synthetic chemical pesticides could be done by using production facilities of organic agriculture in the form of organic fertilizers and synthetic non-chemical pesticides on a larger scale, which base materials are available in nature. The problem faced by farmers in using these inputs is the lack of awareness and skills in producing organic inputs. This community service program with competitive schematics aims to assist the community in preparing local resource-based organic production inputs in Uwe Nuni Village, Palolo District. Specifically, to increase the awareness and skills of farmers in producing organic inputs based on local resources. The method used for counselling and training is Focus Group Discussion (FGD) approach, as well as practice and demonstration plots, which also provide technical guidance on making compost and botanical pesticides, and organic-based plant cultivation techniques. The results of the community service program show that the implementation of counselling and training increases the community’s awareness, skills, and attitudes by 38%, 56% and 54%, respectively. The compost made during the technology training was made from cow and goat manure, while the botanical insecticides were made from quickstick (Gliricidia sepium) plant leaves, papaya leaves, and soursop leaves. These plants are potential resources in Uwe Nuni Village, Palolo District.